2015
DOI: 10.1515/ffp-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Litterfall and growth dynamics relationship with the meteorological variability in three forests in the Montseny natural park

Abstract: We assessed the influence of some environmental conditions (temperature and rainfall) on the litterfall and BAI (basal area increment), in three close forests in the Montseny massif (NE part of the Iberian peninsula, Spain). Two of them are composed of deciduous species Fagus sylvatica and Quercus petraea, and the other one is a Mediterranean evergreen species, Quercus ilex. We have collected monthly data about litterfall and radial growth since 2007. For each forest there are tree plots, with litterfall traps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
4
7
0
2
Order By: Relevance
“…Independently of the study site, litterfall showed a strong seasonal pattern with a major peak in spring (March-June). These results are consistent to those reported for Mediterranean evergreen oaks (Bellot et al 1992, Rapp et al 1999, Bussotti et al 2003, Andivia et al 2013, Bou et al 2015. This seasonal pattern is tightly determined by leaf fall, which constitutes approximately 70% of the total litterfall amount.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Independently of the study site, litterfall showed a strong seasonal pattern with a major peak in spring (March-June). These results are consistent to those reported for Mediterranean evergreen oaks (Bellot et al 1992, Rapp et al 1999, Bussotti et al 2003, Andivia et al 2013, Bou et al 2015. This seasonal pattern is tightly determined by leaf fall, which constitutes approximately 70% of the total litterfall amount.…”
Section: Discussionsupporting
confidence: 91%
“…The amount of litterfall in our study (3.9 Mg ha -1 year -1 ) was similar to those values reported in other studies in Mediterranean cork oak (3.9-5.1 Mg ha -1 year -1 - Caritat et al 1992, Rapp et al 1999, Sá et al 2005 and holm oak forests (3.8-6.9 Mg ha -1 year -1 - Bussotti et al 2003, Andivia et al 2013, Bou et al 2015. Litterfall was greater in Montseny than in Hinojos as might be expected by the greater basal area and wetter climatic conditions in Montseny site (Berg & Laskowski 2005, Roig et al 2005.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, it is found that the mass of reproductive litterfall in a Brazilian tropical dry forest was determined by the dispersal syndromes of the tree species (Souza et al., 2019). Our results showed that the overall contribution of reproductive parts to total litterfall production was ∼15%, which is similar to the value of ∼16% found in Q. ilex forest in the Mediterranean region (Bou et al., 2015). Globally, the contribution of reproductive parts to total litterfall production is dramatically discrepant across various forest types.…”
Section: Discussionsupporting
confidence: 90%
“…Además, el NE de la Península Ibérica se encuentra en un contexto de transición entre les regiones euro-siberianas y las de clima mediterráneo donde se esperen grandes cambios (Thuiller et al, 2005). Pero estos cambios dependen de la vulnerabilidad de cada especie delante del cambio climático, ya que los bosques templados como el hayedo y el robledal de roble albar se prevén que reduzcan su rango de distribución, mientras que los árboles mediterráneos serán menos afectados (Aranda et al, 2000;Fotelli et al, 2009;Banqué et al, 2013;Bou et al, 2015). Si bien el cambio global está siendo un tema muy estudiado, existen pocos trabajos sobre montaña de baja y media altitud, precisamente donde crecen estos bosques al NE de la Península Ibérica.…”
Section: Introductionunclassified